PENGGUNAAN MODEL PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY) UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR IPA KELAS 4 SD - Laksono, Tri; Harjono, Nyoto; Airlanda, Gamaliel Septian (KALAM CENDEKIA PGSD KEBUMEN, 2018)
AbstractThe background of the problem in this study is the lack of learning process in the process of learning so that the effect on the low learning outcomes. This study aims to improve learning and learning outcomes of science grade 4 by applying a guided inquiry learning model on science subjects second semester Kauman Lor State Element 01 years of 2017/2018 pelajaraan. The research used is Classroom Action Research (CAR) which consists of two cycles. Each cycle consists of 3 meetings, each covering several stages, namely action planning, action execution, observation, and reflection. It is known from the research that in the initial conditions before the action that the learning process in the category of good only 3 students (11.53%). After the action in cycle I, the learning process increased to 8 students (30.76%). In cycle II, there is an increase in learning process that is there are 22 students (84.61%) who have good learning process categories. While the results before learning to bealajar action, students who reach KKM = 70 only 7 students (26.92%) of 26 students. After the action is given in cycle I, there is an increase of the learning result which is complete to 16 students (61,53%). In cycle II, there is another improvement of learning achievement to 26 students (100%). Thus it can be concluded that the use of Inquiry Learning Guidance model (Guided Inquiry) can improve the process and the results of science learning in fourth graders of Kauman Lor 01 Elementary School II semester II Lesson Year 2017/2018.Keywords: Guided Inquiry, Learning Process, Learning Outcomes ABSTRAKLatar belakang masalah dalam penelitian ini adalah kurangnya proses belajar dalam proses pembelajaraan sehingga berpengaruh pada rendahnya hasil belajar. Penelitian ini bertujuan untuk meningkatkan proses belajar dan hasil belajar IPA kelas 4 dengan menerapkan model pembelajaraan inkuiri terbimbing pada mata pelajaran IPA semester II SD Negeri Kauman Lor 01 tahun pelajaraan 2017/2018. Penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) yang terdiri dari dua siklus. Setiap siklus terdiri dari 3 pertemuan, masing-masing mencakup beberapa tahap, yaitu perencanaan tindakan, pelaksanaan tindakan, observasi, dan refleksi. Diketahui dari hasil penilitian bahwa pada kondisi awal sebelum dilakukannya tindakan yang proses belajarnya dalam kategori baik hanya 3 siswa (11,53%). Setelah dilakukan tindakan pada siklus I, proses belajar meningkat menjadi 8 siswa (30,76%). Pada siklus II, terjadi peningkatan proses belajar yaitu ada 22 siswa (84,61%) yang memiliki kategori proses belajar baik. Sedangkan hasil bealajar sebelum diadakan tindakan, siswa yang mencapai KKM=70 hanya 7 siswa (26,92%) dari 26 siswa. Setelah diberikan tindakan pada siklus I, terjadi peningkatan hasil belajar yang tuntas menjadi 16 siswa (61,53%). Pada siklus II, terjadi lagi peningkatan kentuntasan hasil belajar menjadi 26 siswa (100%). Dengan demikian dapat disimpulkan bahwa penggunaan model pembelajaran Inkuiri Terbimmbing (Guided Inquiry) dapat meningkatkan proses dan hasil belajar IPA pada siswa kelas 4 SD Negeri Kauman Lor 01 semester II Tahun Pelajaran 2017/2018.Kata Kunci : Inkuiri Terbimbing, Proses Pembelajaran, Hasil Belajar